Vascular Surgery of Limbs in Antananarivo: Indications and Outcomes - Randimbinirina Zl, Rajaobelison T, Randrianandrianina Hf, Rakotoarisoa Ajc, (Pakistan Journal of Medical & Health Sciences, 2022)
Background : The aim of this study was to describe the indications and outcomes for vascular surgery of limbs in Antananarivo. Methods: This was a retrospective and descriptive study for a period of 6 years (01 January 2015 to 31 December 2020), performed at Joseph Ravoahangy Andrianavalona Teaching Hospital Antananarivo, including all patients underwent arterial procedures of limbs. Demographic data, surgical indications, cardiovascular risk factors and history of cardiovascular disease, reason of admission, diagnostic imaging, surgical procedures and outcomes were analyzed. Results : One hundred eighty-nine patients were recorded, including 141 males (74.60%) and 48 women (25.39%). The average age was 48.27years old. The commonest indications of surgical vascular procedures were trauma (33.86%), diabetic peripheral arteriopathy (38.09%) and peripheral arterial disease (12.16%). The most common modifiable risk factors for cardiovascular disease were diabetes mellitus (53.43%), high blood pressure (51.85%), smoking (33.86%). Fourty-one patients (21.69%) had a history of cardiovascular disease. Gangrene (46.03%) and external bleeding (32.27%) were the commonest reason of admission. Surgical procedures were amputation (51.85%), arterial repair (32.80%), Fogarty thromboembolectomy (8.99%), ligation (13.15%) and popliteal cyst excision (3.17%). All revascularization procedures were performed by an open surgery. The overall limb salvage rate was 96.82%. Conclusion: Trauma and diabetic peripheral arteriopathy were the commonest indication of vascular surgery of limbs. Open repair surgery remain the surgical procedure to perform vascular surgery of limbs in our context.